KEMAMPUAN PEMAHAMAN MATEMATIS DIPENGARUHI OLEH TINGGI DAN RENDAHNYA AKADEMIK SEKOLAH - Siti Sa'adah; Siti Elva; Dita Mariyanti; Wahyu Hidayat (Departement of Mathematics Education, 2019)
This study have to analyze examine in depth about ability of mathematical understanding, influenced by the high and low academic schools. The study was design in the form of experiments using linear regression. The population in this research is 2 junior high school student in Cimahi and the sample each as many 33 people determined by purpose sampling technique in each of junior high school in Cimahi. The instrumen in this research is the test of mathematical understanding ability as much as 5 items. Based on the results of this study concluded that, the ability of students to understand mathematically with schools that have a high academic level there are significant differences compared with schools that have a low academic levels.